258 FLEXIT: Geriatric Muscle on the Orthopedic Ward. (16th September 2019) - Reddin, Catriona; Murphy, Robert; Dempsey, Aoife; Kissane, Bláithín; Waters, Ruairi; Murphy, Colin; Egan, Ciara; O'Keeffe, Shaun; Mulkerrin, Eamon; O'Donnell, Martin; Walsh, Thomas; Byrne, Fergus; et al.
Abstract: Background: Older patients post hip fracture benefit from specialist orthogeriatric care. Best practice tariffs incentivising compliance with the Irish Hip Fracture Standards (IHFS) have been introduced in Ireland (1) . We compared levels of compliance to IHFS before and after introduction of a dedicated orthogeriatric service in a tertiary referral hospital. We also hypothesized that improved continuity of care by regular orthogeriatric review would result in less general medical consults to medical teams. We looked at the number of inpatient consults sent for each time period and compared the number of general medical consults sought by orthopaedic teams for similar time periods. Methods: Data was prospectively collected on all hip fracture patients seen by the orthogeriatric service from Aug 2018-Feb 2019 and was retrospectively compared with patients admitted with hip fractures from Aug 2017-Feb2018. Results: Similar numbers of patients were seen in each time period (n=146 v n=139) with similar age profiles (81.8 vs 79.6 years). Improvements were seen in all of the six IHFS. The most significant improvements were an increase from 31.2% to 96.5% in the proportion of patients seen by a Geriatrician, and an increase from 7.4% to 98.5% in those who had a formal falls assessment. Fewer patients required medical team consults after the service began (32.2% vs 46.8%, p=0.016). The resultant total number of consults sent fell from 120 consults to 59 consults. Conclusion: Introduction of an orthogeriatric service has substantially improved compliance with IHFS. The reduction in the number of medical consults requested by orthopaedic teams reflects the improved quality and continuity of care for these patients.